2021
DOI: 10.1371/journal.pone.0247885
|View full text |Cite
|
Sign up to set email alerts
|

Association ankle function and balance in community-dwelling older adults

Abstract: Background and purpose Ankle function declines with age. The objective of this study was to investigate the association between ankle function and balance in older adults, with a focus on range of motion (ROM) and strength. Methods This was a cross-sectional study that included 88 healthy community-dwelling older adults. Ankle mobility was measured while bearing weight (lunge test) and not bearing weight. The plantar-flexor muscle strength was assessed using a hand-held dynamometer. Balance was measured in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…31 These inconsistencies could also be attributable to other biomechanical factors that impact dynamic balance, such as muscle strength, ankle mobility, and functionality of synovial structures that may enhance joint stiffness and thus limit dynamic balance. [36][37][38] This assumption was also confirmed by Hoch et al 39 in their investigation, where they concluded that a loss of ankle range of motion could negatively affect dynamic balance.…”
Section: Main Findingssupporting
confidence: 64%
“…31 These inconsistencies could also be attributable to other biomechanical factors that impact dynamic balance, such as muscle strength, ankle mobility, and functionality of synovial structures that may enhance joint stiffness and thus limit dynamic balance. [36][37][38] This assumption was also confirmed by Hoch et al 39 in their investigation, where they concluded that a loss of ankle range of motion could negatively affect dynamic balance.…”
Section: Main Findingssupporting
confidence: 64%
“… 34 Therefore, studies regarding ankle function in patients with stroke have mainly reported that ankle dorsiflexion ROM and plantar flexor strength were effective in the performance of functional activities rather than ankle proprioception. 35 However, another study suggested that uncertainty regarding the foot position due to impaired ankle proprioception during walking could alter the step length and affect walking speed. 36 Depending on the lesion location, strokes can damage both motor and sensory neural systems, thereby leading to neurologic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the goniometer, which seems to have been used in clinical practice as ‘a proxy’ for joint function assessment may be a useful tool in assessing locomotor capacity. In fact, in clinical research, this tool has rather been used to assess range of motion [ 148 ], even if there seems to be a confusion between range of motion and joint function in some publications [ 149 , 150 ].…”
Section: Discussionmentioning
confidence: 99%